Sugar Quality Produced from Immature and Mature Sugarcane Damaged by Spittlebugs - Madaleno, Leonardo Lucas; Ribeiro, Natália Novais [UNESP]; Ravaneli, Gisele Cristina [UNESP]; Stupiello, José Paulo; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Springer Nature, 2023)
Spittlebugs are known for reducing the quality of sugarcane. However, the sugar process and crystals produced from damaged sugarcane have not been fully characterized. Furthermore, the proper maturation status of sugarcane could influence the results found for sugar production. This paper aimed to evaluate spittlebugs' interference with sugarcane (SP80-1842), clarified juice, and raw sugar quality in two harvest periods with immature and mature sugarcane. A completely randomized factorial design with three replications was conducted. The first factor was spittlebug damage in stalks: healthy (0% damage) and injured stalks (15, 30, and 60%). The second factor was the harvest periods with the same sugarcane plantation: May–June (with immature stalks) and October (with mature stalks). The results also show that for sugarcane, soluble solids, sucrose, and pH decreased, and the fiber increased in samples with a higher quantity of damaged stalks. With immature sugarcane, 30% of pest damage caused by spittlebugs increased by 41% in phenolic compounds, 39% in color, 29% in ash, and 22% in final crystal moisture. The sugar color is higher because of the increasing phenol compounds provided by spittlebug damage to the raw material. These molecules were not removed by clarifying juice from immature stalks. On the other hand, with proper sugarcane maturation conditions, the level of damaged stalks did not interfere with sugar quality. Therefore, choosing the best moment for harvest could reduce the impacts of the pest on the quality of crystals produced.
Keywords: Clarification; Extracted juice; Mahanarva fimbriolata; Raw sugar; Saccharum spp; Stalk damage